No-till Farming: The Way of the Future for a Sustainable Dryland Agriculture - Papendick, R I; Parr, J F (Annals of Arid Zone, 2016)
Most dryland farming systems depend on tillage to grow crops. There is overwhelming evidence that repeated tillage is destroying the soil resource base and causing adverse enviromnental impacts. Tillage degrades the fertility of soils, causes air and water pollution, intensifies drought stress, destroys wildlife habitat, wastes fuel energy, and contributes to global warming.Consequently, most tillage-based systems in a dryland environmental are not sustainable in the long-term. Today, dryland farmers are expected to produce food in ever greater quantities. This is becoming more difficult to do in view of declining soil quality, most of which is caused by soil tillage. It is becoming well documented scientifically that continuous no-till is the most effective, and practical approach for restoring and improving soil quality which is vital for sustained food production and a healthy environment. With this way of farming crop, residues or other organic amendments are retained on tlle soil surface and sowing/fertilizing is done with minimal soil disturbance. Research and farmers experience indicate that with continuous no-till soil organic matter increases, soil structure improves, soil erosion is. controlled, and in time crop yields increase substantially from what tlley were under tillage management, due to improved water relations and nutrient availability. TIlese changes help to promote a cleaner and healtllier enviromnent and a more sustainable agriculture. A major obstacle that fanners often face with change to continuous no-till is overcoming yield-limiting factors during the transition years, that is, tlle first years of no-till following a history of intensive conventional tillage. These factors are often poorly lU1derstoodand may be biologically-driven. Some of the problenls involve residue management and increased weed and disease infestations. Fanner experience seems to indicate that many problems during the transition are tenlporary and become less important as the no-till system matures and equilibrates. The judicious use of crop rotations, cover crops and some soil disturbance may help reduce agronomic risks dming tlle transition years. Farmers switching to continuous no-till must often seek new knowledge and develop new skills and techniques in order to achieve success with this new and different way of fanning. Answers to their questions are urgently needed to provide strategies for promoting no-till as a way to enhance agricultural sustainability for future generations.